2017
DOI: 10.1098/rstb.2016.0252
|View full text |Cite
|
Sign up to set email alerts
|

Timing avian long-distance migration: from internal clock mechanisms to global flights

Abstract: Please refer to our instructions for authors for full details on manuscript preparation. Please note that this template should act as a guide on content, but doesn't necessarily need to be followed for style and formatting. Our typesetters will set your manuscript into house style after acceptance.*Author for correspondence (Susanne.akesson@biol.lu.se). †Present address: Department of Biology, Lund University, Ecology Building, SE-223 62 Lund, Sweden 2 Summary Migratory birds regularly perform impressive long-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
101
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 101 publications
(113 citation statements)
references
References 175 publications
(365 reference statements)
10
101
2
Order By: Relevance
“…Ecological studies of migratory birds also echo the findings on chronotypes described above for chronobiology (figure 3). Studies of repeated journeys of individuals in some species have revealed between-individual variation in combination with high individual consistency [16,[93][94][95][96]. Similar findings have been reported for daily behaviours of animals, where chronotype has become an increasingly popular measure [55,[97][98][99][100][101].…”
Section: (B) Ecologysupporting
confidence: 69%
See 4 more Smart Citations
“…Ecological studies of migratory birds also echo the findings on chronotypes described above for chronobiology (figure 3). Studies of repeated journeys of individuals in some species have revealed between-individual variation in combination with high individual consistency [16,[93][94][95][96]. Similar findings have been reported for daily behaviours of animals, where chronotype has become an increasingly popular measure [55,[97][98][99][100][101].…”
Section: (B) Ecologysupporting
confidence: 69%
“…Extensions include tracking of individuals across the lifespan or in the context of conspecific interactions. One group whose timing has been studied in particular detail are migratory birds, which exploit annual resource peaks across the globe [16]. Very much in parallel to findings in chronobiology, ecological studies on these and other groups have demonstrated various degrees of plasticity in timing, for example, in response to weather or between seasons.…”
Section: (B) Ecologymentioning
confidence: 99%
See 3 more Smart Citations